SUPREMASI KONSTITUSI DI TENGAH LEGISLASI CEPAT: URGENSI PENGUATAN WEWENANG MAHKAMAH KONSTITUSI - Mochammad Farhan; Utang Rosidin (Yayasan Baitul Hikmah al-Zain, 2025)
This article examines the urgency of strengthening the authority of Indonesia’s Constitutional Court (MK) in addressing the threat of fast-track legislation to constitutional supremacy. Using normative legal research, the study analyzes cases such as the Job Creation Law (UU Cipta Kerja), the National Capital City Law (UU IKN), and revisions to the Constitutional Court Law. Findings reveal that fast-track legislation often neglects democratic principles, such as public participation and transparency, resulting in laws that are vulnerable to procedural and substantive flaws. The Constitutional Court, as the guardian of the constitution, faces limitations in reviewing such laws due to political pressures, limited access to legislative documents, and weak enforcement mechanisms. The article proposes legal reforms, including expanding the scope of judicial review, enhancing the enforceability of MK’s decisions, and increasing public accessibility to constitutional challenges. Strengthening MK’s authority is critical to ensuring constitutional compliance, protecting citizens’ fundamental rights, and maintaining democratic integrity in Indonesia’s legal system.